Odpowiedzi

2009-10-13T15:19:51+02:00
X+2y+3z=6
x=1 1+2*1=3*1=6
y=1
z=1

2x+3y-z=4
x=2 2*2+3*1-3=4
y=1
z=3

3x+y-4z=0
x=1 3*1+1-4*1=0
y=1
z=1
2009-10-13T15:22:43+02:00
X = 1
y = 1
z= 1

x+2y+3z= 1+2+3=6
2x+3y-z= 2+3-1=4
3x+y-4z= 3+1-4+0
Najlepsza Odpowiedź!
2009-10-13T15:23:47+02:00
X+2y+3z=6
2x+3y-z=4
3x+y-4z=0

x = 6 - 2y - 3z
-z = 4 - 2x - 3y /*(-1)
3x+y-4z=0

x = 6 - 2y - 3z
z = -4 + 2x + 3y
3x+y-4z=0

x = 6 - 2y - 3(-4 + 2x + 3y)
z = -4 + 2x + 3y
y = 4z - 3x

x = 6 - 2y - 3[-4 + 2x + 3y]
x = 6 - 2y + 12 - 6x - 9y
x + 6x + 2y + 9y = 18
7x + 11y = 18
7x = 18 - 11y /:7
x = ¹/₇*(18 - 11y)

z = -4 + 2x + 3y
z = -4 + 2[¹/₇*(18 - 11y)] + 3y
z = -4 + ²/₇*(18 - 11y) + 3y
z = -4 + ³⁶/₇ - ²²/₇y + 3y
z = -4 + 5 ¹/₇ - 3 ¹/₇y + 3y
z = 1 ¹/₇ - ¹/₇y

3x+y-4z=0
2(¹/₇*(18 - 11y)) + y - 4(1 ¹/₇ - ¹/₇y) = 0
²/₇*(18 - 11y) + y -4 ⁴/₇ + ⁴/₇y = 0
³⁶/₇ - ²²/₇y + y - 4 ⁴/₇ + ⁴/₇y = 0
5 ¹/₇ - 3 ¹/₇y + y - 4 ⁴/₇ + ⁴/₇y = 0
- 3 ¹/₇y + y + ⁴/₇y = -5 ¹/₇ + 4 ⁴/₇
-2 ⁸/₇y + y + ⁴/₇y = -³⁶/₇ + ³²/₇
-1 ⁴/₇y = -⁴/₇
-¹¹/₇y = -⁴/₇ /*(-⁷/₁₁)
y = ⁴/₁₁